The Perception of Eros and the Cinema Audience Experience in Cádiz (Spain) - Inmaculada Rodríguez-Cunill; Juan José Domínguez-López; Sonia Carlos-García (Societies, 2024)
The perception of the concept of Eros has evolved through shared cinematic experiences, to the point of shaping collective imagery in Cadiz, Spain. This city is known for its creativity and an extraordinary amount of performances during the period of carnival, and is represented annually by anonymous citizens. The research method employed consisted of an exhaustive analysis of bibliographic, press, and archival references on audience behavior from the introduction of the cinematograph to the present day. The authors have designed a table that organizes the emergence of movie theaters in the city and completed the background information, delving into the historical, geographical, and idiosyncratic factors that have contributed to collective creativity in the city. From there, we analyzed the evolution of the concept of Eros through the perspectives of Byung Chul Han and Georges Bataille. As a result, we recovered the value of projection interruptions in the analog environment as an opportunity for collective interaction, confronting them with the demands of technological perfection. We demonstrated the resilience of the analog through new experiences that show the evolution of the need for collective contact. Future studies will focus on other contexts, such as supermarkets and terraces, to contribute to a broader understanding of urban spaces, social cohesion, and perceptions of Eros.